Embedding Ta'awun in Aqidah Akhlak Learning: A Character Education Framework from Indonesian Islamic Boarding Schools - Abdul Rahman; Rosmaimuna Siregar; Mira Rahmayanti Sormin (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study aims to analyze the concept and implementation of Ta'awun (mutual assistance) in Aqidah Akhlak (Theology and Morals) learning at Pondok Pesantren Al-Ansor, Padangsidimpuan City. Ta'awun as a fundamental Islamic value is considered crucial in shaping the character of students (santri) in a pesantren environment that emphasizes communal life. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews with teachers and students, and document studies. The collected data were analyzed using Miles and Huberman's qualitative data analysis technique, which includes data reduction, data presentation, and conclusion drawing/verification. The results show that the concept of Ta'awun is comprehensively understood and implemented in real terms in daily life at the pesantren, both in academic activities (such as study assistance), daily activities (such as communal cleaning and duty schedules), and in social interactions both inside and outside the pesantren. This implementation is supported by the boarding system, the exemplary role of the ustadz/ustadzah (teachers), and the integration between theoretical learning in the classroom and direct practice. However, the study also identified several inhibiting factors, such as varying levels of student self-awareness and limitations in supervision time. In conclusion, Pondok Pesantren Al-Ansor has successfully made Ta'awun a pillar in forming students' character to be caring, empathetic, and collectively responsible, which aligns with the pesantren's vision to produce clerics who contribute to society.